The Socio-Cultural of the Tiong Bu'u Village Community around the KPHL Unit XII Batu Rook, Indonesia - Awaluddin Aziz; Aris Pudji Hadi; Muhammad Furkan; Karmilasanti, Karmilasanti; Nurfadhilah Yusuf (Cita konsultindo, 2024)
The Forest Management Unit (KPH) plays a crucial role in the context of national forestry development. The Protected Forest Management Unit (KPHL) Unit XII Batu Rook will be encouraged to become operational. The activity of Social and Cultural Inventory in and around the KPHL area aims to obtain data and information used for long-term, medium-term, and short-term strategic planning and policy formulation. This research utilizes both qualitative and quantitative methods. The collected data includes village history, settlements and land use, community systems and structures, community interactions with forest areas, threats and pressures, as well as opportunities and community support for forest existence. Based on the inventory results, the majority of Tiong Bu'u Village is forest area. The indigenous people of Tiong Bu'u Village have a high dependence on the forest, not only for farming but also for both wood and non-wood forest products for their personal needs and cultural traditions. The community in Tiong Bu'u Village lacks hierarchical and social structures that bind community life. The majority of the population possesses local wisdom in utilizing, conserving, and sustaining the forest. The high dependence of the community on the forest indicates to KPHL Unit XII Batu Rook the importance of engaging the community in forest management through partnership schemes or towards the formation of community empowerment blocs.